Arbuscular Mycorrhizal Fungi Inoculation Improves Flower Yield and Postharvest Quality Component of Gerbera Grown under Different Salinity Levels - Yahia A. Othman; Monther Tahat; Kholoud M. Alananbeh; Malik Al-Ajlouni (Agriculture, 2022)
High salinity levels of irrigated water and the accumulation of salt over time in the soil is a major concern worldwide, including in Jordan. The objective of this two-year study was to assess the influence of arbuscular mycorrhizal fungi (AMF) inoculation on the physiology, yield, and flower quality of gerbera (Gerbera jamesonii cvs. Beaudine and Palm Beach) under different salinity levels (0.0, 20.0 and 40.0 mM-NaCl). The study was arranged in a randomized complete block design with five replicates. During the experimental period (2018–2019), chlorophyll content index (SPAD), leaf gas exchange (photosynthesis, Pn; stomatal conductance, gs; transpiration, E), flower yield, flower quality (pedicel length and diameter, number of days to flowering, flower diameter, and vase life), root sporulation, and colonization were measured. Irrigation with saline water (20 and 40 mM-NaCl) significantly increased salt accumulation in soil. The mean soil electrical conductivity (EC) after two growing seasons for the 20 mM-NaCl treatment was 2.9 dS m−1 and 4.4 dS m−1 for the 40 mM. High salinity level (40 mM-NaCl) reduced root AMF sporulation by 53–62% and colonization by 12–25% across cultivars. Interestingly, root colonization was higher than 50% across salinity level and in both cultivars. Saline water at 40 mM-NaCl significantly reduced SPAD, Pn, gs, E, flower yield, and quality component, especially vase life. Interestingly, leaf chlorophyll content index from AMF-inoculated plants was significantly higher than uninoculated ones across cultivars at the second growing season. In addition, inoculation with AMF significantly increased yield in both ‘Beaudine’ (34–40%) and ‘Palm Beach’ (42–44%) cultivars and across the study period, 2018 to 2019. In addition, AMF increased vase life in ‘Beaudine’ by 19% to 28% and in ‘Palm Beach’ by 21% to 22%. Overall, our results revealed that gerbera growers can increase their flower yield and postharvest flower quality component (vase life) under saline conditions (soil EC < 4.4 dS m−1) by inoculating the seedlings with AMF.